Doing More With Written Feedback: Improving Learner Satisfaction and Reflection With the LEAF (Learner-Engaged Analysis of Feedback) Method. (16th March 2021) - Saddawi-Konefka, Daniel; Sullivan, Amy; Beltran, Christine; Baker, Keith
Abstract : Supplemental Digital Content is available in the text. Abstract : Problem: Written feedback is often overly positive, nonspecific, and difficult to interpret. Learner satisfaction with written feedback is low and obtaining written feedback that encourages self-reflection is challenging. Improving feedback quality is laborious and only modestly effective. Approach: The authors developed the LEAF (Learner-Engaged Analysis of Feedback) method to improve learner satisfaction with, and reflection on, existing written feedback. The method pairs a learner and coach to methodically identify themes in the learner's written feedback. Themes occurring more frequently or less frequently than typical offer areas for reflection, as they may identify learners' relative strengths or weaknesses. The method was introduced at the Massachusetts General Hospital in 2017 during program director (PD) meetings with anesthesiology residents. In 2018, resident satisfaction was measured (1 to 5 Likert-type questions, 1 = "not at all satisfied, " 5 = "extremely satisfied") for 4 feedback sources, 2 related to the LEAF method (PD meetings, written feedback) and 2 unrelated (verbal feedback, mentor feedback). Residents' comments were qualitatively assessed to explore the impact on self-reflection. Outcomes: Residents who had participated in a LEAF session (n = 54), compared with those who had not (n = 11), reported higher satisfaction with written feedback (mean 3.1 versus 2.5, d = 0.53, P = .03) and PD meeting feedback (mean 3.8 versus 2.8, d = 0.80, P = .03). There were no significant differences between groups for satisfaction with feedback unrelated to the LEAF method. Qualitative analysis of comments suggested that residents found the method useful for providing holistic self-assessment, facilitating goal setting, uncovering blind spots, and improving feedback interpretation. Next Steps: Next steps should include studies determining if the association between increased learner satisfaction with written feedback and the LEAF method is causal, and whether this feedback process changes learners' subsequent behaviors.